Can trading partner cultural diversity explain trade?. Issue 2 (3rd April 2019) - Gani, Azmat; Scrimgeour, Frank
Abstract: The importance of culture on economic outcomes has been an element of ongoing research mainly in the disciplines outside of mainstream economics such as sociology and anthropology. From an economic perspective, there is a strong feeling among the corporate community that culture can be influential in business dealings. International trade is one area of business where cultural diversity can matter. This paper investigates the effect of trading partner cultural diversity on trade within the gravity model framework. The gravity model incorporates four measures to capture cultural diversity: religion, ethnicity, language and legal origin. Using data on New Zealand's trade with Asia and employing the panel corrected standard errors estimation procedure, the empirical findings reveal that Asian diversity in religion and languages is positively correlated with New Zealand–Asia trade. The results reveal that the expected effects of standard gravity variables, and we conclude that the cultural diversity of trading partners positively influences international trade.